Useful Ideas when Taking Songs to a Class (2003)
ABSTRACT: This article gives some basic ideas when teaching English with songs and also somereasons why EFL teachers take songs to class. It addresses two important issues whenteaching with songs: selection of songs and preparation of tasks, examples for eachkind of task are given. This paper recommends a routine of designing tasks that followthe format of pre-listening activities, while-listening activities and post-listening activities.Key words: designing tasks, music, teaching EnglishEste artículo brinda algunas ideas importantes para la enseñanza de inglés con música.Da algunas razones sobre porque los profesores de inglés como lengua extranjera (EFL)llevan canciones a sus quehaceres docentes. Señala dos consideraciones importantespara tener en cuenta cuando se enseña con canciones: la selección de las canciones yla preparación de las actividades. Además, recomienda una rutina de diseño de activida-des que sigue el formato de pre, mientras y post actividades de escucha.Palabras claves: diseño de tareas, música, enseñanza de inglés.Cet article offre quelques idées importantes pour un enseignement de l’anglais en musique,et les raisons qui poussent les professeurs d’anglais langue étrangère à développerleurs savoirs-faire professionnels au niveau du chant. Sont mis en relief également deuxéléments à prendre en compte dans l’enseignement en chanson: la sélection des chansonset la préparation des activités. Enfin, voici la recommandation d’un modèle de planificationsuivant le cadre de pré-activités, déroulement des activités et post-activités.Mots clés : planification d’activités, musique, enseignement de l’anglais.